Design, Synthesis, Characterization and in vivo Antidiabetic Activity Evaluation of Some Chalcone Derivatives - Welday Kahssay S; Hailu GS; Taye Desta K (Dove Medical Press, 2021)
Semere Welday Kahssay,1 Gebremedhin Solomon Hailu,2 Kebede Taye Desta3 1Mizan-Tepi University, College of Health Sciences, School of Pharmacy, Department of Pharmaceutical Chemistry, Mizan-Aman, Ethiopia; 2Mekelle University, College of Health Sciences, School of Pharmacy, Department of Medicinal Chemistry, Mekelle, Ethiopia; 3Adama Science and Technology University, College of Applied Science, Department of Applied Chemistry, Adama, EthiopiaCorrespondence: Semere Welday Kahssay Tel +251-904-296-810Fax +251-344-416-681Email semere0409@gmail.comBackground: Diabetes is one of the growing health problems worldwide, and scientists have been striving to find effective treatment methods. In this regard, chalcones have frequently been targeted by many researchers owing to their diverse biological activities.Methods: Here, the Claisen-Schmidt condensation reaction was applied to synthesize five chalcone derivatives. The chalcone derivatives were evaluated for their relative antidiabetic activities in vivo using streptozotocin (STZ)-induced diabetic mice. Besides, the compounds were assessed for their reduction in postprandial hyperglycemia at 50 and 100 mg/kg dose levels against a standard drug, glibenclamide. In addition, the structure-activity relationship (SAR) was analyzed to determine the effect of structural modification in chalcones activity.Results: A dose-dependent reduction in postprandial hyperglycemia was observed. The highest reduction in blood glucose level (BGL) was achieved by compound 3 at a dose of 100 mg/kg (39%). This was found to be even higher than glibenclamide (34.5%). In the STZ-induced diabetic animal model, all test compounds showed comparable efficacy with glibenclamide. The SAR analysis revealed that the incorporation of electron-donating groups at position 5 of the benzaldehyde ring and position 2 of the acetophenone ring is promising to increase the antihyperglycemic activities of chalcones.Conclusion: The chalcone derivatives considered in this study could be used as potential lead compounds in the discovery of effective drugs to treat diabetes mellitus.Keywords: antidiabetic, chalcone, diabetes mellitus, structure-activity relationship, streptozotocin, characterization, in vivo